København-Kairo, tur-retur: En sikkerhedsteori møder revolutionen - Greenwood, Maja Touzari Janesdatter; Wæver, Ole (Politik, 2012)
Though Securitization theory has been applied to cases worldwide, it has been criticized for limited applica- bility to the non-western world. When, in 2010, Centre for Advanced Security eory began a collaboration with Danish Egyptian Dialogue Institute and Al-Ahram Centre for Political and Strategic Studies in Cairo, Securitization theory was challenged on two levels: e theory was to both analyse and act politically in a Middle Eastern context, and then during the Arab Spring, the role of the entire Egyptian security sector was reevaluated. ese unique circumstances prompted re ections on the use of non-traditional and traditional security concepts, how the Egyptian revolution could be understood through Securitization eory, as well as what the experiences of this project will mean for further theory development. is article discusses these points in light of the Danish delegation’s experiences.